Cyclic fatigue resistance of EdgeTaper Platinum, Protaper Gold, and TruNatomy Prime rotary files before and after autoclave sterilization - Almohareb,Rahaf A.; Barakat,Reem M.; Algahtani,Fahda N.; Alkadi,Manal F. (PeerJ, 2023)
Background This in vitro investigation aimed to determine the influence of multiple autoclave cycles on the cyclic fatigue resistance of three heat-treated nickel-titanium (NiTi) files: EdgeTaper Platinum (ETP), ProTaper Gold (PTG), and TruNatomy Prime (TN). Materials Sixty NiTi files, twenty of each NiTi file type: ETP 25/.06, PTG 25/.08, and TN 26/.04 were randomly divided into four equal subgroups (n = 5). The files for the control group were left un-autoclaved. Different autoclave sterilization cycles (one, five, and ten) were used for the other three groups. The files were then placed in a metal canal block and rotated according to the manufacturer’s instructions until fracture. The length of the broken segment and the time taken for fracture were measured. The fractured surfaces were subsequently subjected to SEM imaging. The Kruskal-Wallis test was used to analyze the data, followed by Dunn-Bonferroni pairwise comparisons. Statistical significance was set at p < 0.05. Results ETP showed significantly greater resistance to cyclic fatigue than TN in all autoclave groups and PTG after five autoclave cycles (p = 0.014). Fatigue resistance was not affected by the number of autoclaving cycles, except for ETP. After the first and tenth autoclaving cycles, they required significantly more rotations to failure than the non-sterilized files (p = 0.039 and p = 0.021, respectively). The fractured segments of the ETP files in these two groups were also longer than those in the control group (p = 0.010). Conclusion The cyclic fatigue resistance of ETP was greater than that of TN in all tested conditions. Repeated autoclave cycles of sterilization improved the cyclic fatigue resistance of the ETP files only and did not affect the cyclic fatigue resistance of TN and PTG. However, the ETP files separated at a longer distance from the tip with increased autoclaving cycles.
Keywords: Autoclave; Cyclic fatigue; Edgetaper platinum; Trunatomy; Heat-treated file; Nickel-titanium; Rotary files